Clinical Efficacy and Safety of Chondroitin Combined with Glucosamine in the Treatment of Knee Osteoarthritis: A Systematic Review and Meta-Analysis. (25th July 2022) - Wang, Zhiyao; Wang, Rongtian; Yao, Hui; Yang, Jianying; Chen, Yuefeng; Zhu, Yuqi; Lu, Chao
Abstract : Objective . This analysis was aimed at providing evidence-based medicine basis for systematic evaluation of chondroitin combined with glucosamine in the treatment of knee osteoarthritis. Methods . The randomized controlled trials (RCTs) of chondroitin combined with glucosamine in the treatment of knee osteoarthritis (KOA) were searched in PubMed, EMBASE, ScienceDirect, Cochrane Library, China Knowledge Network Database (CNKI), China VIP Database, Wanfang Database, and China Biomedical Literature Database (CBM) online database. The retrieval time ranges from the database creation to the present. Two investigators gathered the information individually. The risk of bias was assessed using the criteria of the Cochrane back review group. RevMan5.4 statistical software analyzed the selected data. Results. A total of 6 RCT articles were obtained. Overall, 764 samples were evaluated by meta-analysis. The clinical efficacy of chondroitin combined with glucosamine was significantly better than that of routine treatment by meta-analysis. The confidence interval of 95% was (4.86, 17.08) (Z = 6.89, P < 0.00001 ). The scores of joint pain, tenderness, swelling, and dysfunction in patients with knee osteoarthritis treated with chondroitin combined with glucosamine were significantly lower than those treated with routine treatment. There was no significant difference in the incidence of adverse reactions between chondroitin combined with glucosamine and single treatment of KOA. Due to the small number of documents included in the analysis, it is not suitable to make a funnel chart, but there may be some publication deviation in the analysis. Conclusion. Chondroitin combined with glucosamine is more effective than chondroitin or glucosamine alone in the treatment of KOA and deserves clinical promotion. However, this conclusion still needs to be supported by multicenter, high-quality, double-blind, large-sample randomized controlled clinical trials due to the limitations of the six trials included.